The Extent of Inclusion the Concepts of Sustainable Development in Content of Islamic Studies for the for third level in intermediate school in Saudi Arabia - Almalki, Abdulwahab Abdullah; Alqarni, Mohammed Saad (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to analyze the content of the of Islamic Studies textbooks for the for third level in intermediate school in Saudi Arabia in the light of sustainable development concepts, To achieve the objectives of the study, the researcher used descriptive content analysis-based and adopted the theme and the idea as unit of analysis and the concepts of sustainable development as a group for analysis.. The study sample comprised the three Islamic Studies textbooks for the third intermediate grade. The results of the study indicated that the level of including dimensions of sustainable development was in varying degrees. The social dimension was ranked first with the highest percentage 24% of the total concepts includes 288 sustainable, then the environmental dimension percentage 14% of the total concepts total of 26 sustainable. The findings of the study culminated in a set of recommendations, chief among them the necessity of realizing a balanced inclusion of the sustainable development concepts related to the environmental, social, in the Islamic Education textbook for the third intermediate grade; and inclusion of further sustainable development concepts pertaining to the environmental, social dimension.